Clinical study of breast lump-triple assessment does help in diagnosing it better - Shah, Priti Prasad; Shaikh, Shama; Panchbhai, Sunil; Vakhariya, Bahul (International Surgery Journal, 2018)
Background: Breast cancer is most frequently diagnosed cancer among women and also most common cause of cancer death among women. Early stage detection is still low and is the major reason for poor treatment outcomes in our country. Most of the breast lumps are benign. However, it is important to rule out malignancy. This prospective clinical study is done to evaluate role of triple assessment (clinical examination, mammography and histopathology) in diagnosing breast lump. Methods: All women admitted with the symptoms and signs of breast lump at our hospital were studied in the period of 2 years from July 2014 to June 2016. The findings of physical examination and mammographic examination with histopathological diagnosis were noted n compared. Results: Physical examination of breast lumps is overall less accurate as compared to mammography. There is a tendency to over diagnose malignancy on physical examination. Mammography is more sensitive and specific in the diagnosis of palpable breast lumps as compared to physical examination. Histopathology confirms the diagnosis. Conclusions: It is better to do all three that is clinical examination, mammography and histopathology for all breast lumps diagnosis.